STABILITY AND ROLL EFFECT OF THE STRAIGHT TRUCK SUSPENSION SYSTEM - Harun, M.H.; Hudha, K.; Samin, P.M.; Bakar, S.A.A.; Ubaidillah, U. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Safety and stability control especially those involving rollover motion are essential features of heavy vehicles. Therefore, this study concentrates on identifying the stability and roll effect on the front and rear straight truck suspension system. The straight truck roll motion is modeled in MATLAB/Simulink software and validated using TruckSim software. The behavior of the straight truck is identified when the truck right side tires hit the road bumps to generate the roll motion. The simulation results demonstrate that the rear suspension system is adequately more stable compared to the front suspension system based on the lower root mean square (RMS) value and shorter settling time.